2022
DOI: 10.1155/2022/8189610
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Tool to Predict the Overall Survival of High-Grade Osteosarcoma Patients after Neoadjuvant Chemotherapy: A Large Population-Based Cohort Study

Abstract: Background. The goal of this study was to discover clinical factors linked to overall survival in patients with high-grade osteosarcoma who had received neoadjuvant therapy and to develop a prognostic nomogram and risk classification system. Methods. A total of 762 patients with high-grade osteosarcoma were included in this study. In the training cohort, Cox regression analysis models were used to find prognostic variables that were independently linked with overall survival. To predict overall survival at 3, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Qian et al found that in addition to AJCC stage, patients' age, gender, race, and tumor grade were independently related to the prognosis of esophageal adenosquamous carcinoma ( 9 ). In addition, Huang et al conducted prognostic analysis and constructed a survival prediction model for osteosarcoma patients who received nCT ( 10 ). Unfortunately, there was still limited studies focusing on constructing a nomogram model to predict the survival of EC patients receiving nCT.…”
Section: Introductionmentioning
confidence: 99%
“…Qian et al found that in addition to AJCC stage, patients' age, gender, race, and tumor grade were independently related to the prognosis of esophageal adenosquamous carcinoma ( 9 ). In addition, Huang et al conducted prognostic analysis and constructed a survival prediction model for osteosarcoma patients who received nCT ( 10 ). Unfortunately, there was still limited studies focusing on constructing a nomogram model to predict the survival of EC patients receiving nCT.…”
Section: Introductionmentioning
confidence: 99%